Paving the way towards effective plant-based inhibitors of hyaluronidase and tyrosinase: a critical review on a structure-activity relationship - Jakub Gębalski; Filip Graczyk; Daniel Załuski (Taylor & Francis Group, 2022)
Human has used plants to treat many civilisation diseases for thousands of years. Examples include reserpine (hypertension therapy), digoxin (myocardial diseases), vinblastine and vincristine (cancers), and opioids (palliative treatment). Plants are a rich source of natural metabolites with multiple biological activities, and the use of modern approaches and tools allowed finally for more effective bioprospecting. The new phytochemicals are hyaluronidase (Hyal) inhibitors, which could serve as anti-cancer drugs, male contraceptives, and an antidote against venoms. In turn, tyrosinase inhibitors can be used in cosmetics/pharmaceuticals as whitening agents and to treat skin pigmentation disorders. However, the activity of these inhibitors is stricte dependent on their structure and the presence of the chemical groups, e.g. carbonyl or hydroxyl. This review aims to provide comprehensive and in-depth evidence related to the anti-tyrosinase and anti-Hyal activity of phytochemicals as well as confirming their efficiency and future perspectives.